A Mini Review on Surface-Enhanced Raman Scattering based Nanoclusters for Sensing and Imaging Applications - Chokkareddy, Rajasekhar; Kanchi, Suvardhan; Inamuddin (Current Analytical Chemistry, 2022)
Background: The invention of Surface Enhanced Raman Scattering by adsorbing molecules on nanostructured metal surfaces is a milestone in the development of spectroscopic and analytical techniques. Important experimental and theoretical efforts were geared towards understanding the Surface Enhanced Raman Scattering effect (SERS) and evaluating its significance in a wide range of fields in different types of ultrasensitive sensing applications. Methods: Metal nanoclusters have been widely studied due to their unique structure and individual properties, which place them among single metal atoms and larger nanoparticles. In general, the nanoparticles with a size less than 2 nm are defined as nanoclusters (NCs) and they possess distinct optical properties. In addition, the excited electrons from absorption bands result in the emission of positive luminescence associated with the quantum size effect in which separate energy levels are produced. Results: It is demonstrated that fluorescent-based SERS investigations of metal nanoparticles show more photostability, high compatibility, and good water solubility, which has resulted in high sensitivity, better imaging and sensing experience in biomedical applications Conclusion: In the present review, we report recent trends in the synthesis of metal nanoclusters and their applications in biosensing and bio-imaging applications due to some benefits, including cost-effectiveness, easy synthesis routes and less consumption of sample volumes. Outcomes of this study confirm that SERS-based fluorescent nanoclusters could be one of the thrust research areas in biochemistry and biomedical engineering.
Keywords: sensing and imaging